1997
DOI: 10.1074/jbc.272.36.22447
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific DNA Binding and Transcriptional Regulation by the Promyelocytic Leukemia Zinc Finger Protein

Abstract: Chromosomal translocation t(11;17)(q23;21) is associated with a retinoic acid-resistant form of acute promyelocytic leukemia. The translocation fuses the RAR␣ gene to the PLZF gene, resulting in the formation of reciprocal fusion proteins, hypothesized to play prominent roles in leukemogenesis. Promyelocytic leukemia zinc finger (PLZF) encodes a transcription factor with nine Krü ppel-like zinc fingers, seven of which are retained in the t(11;17) fusion protein RAR␣-PLZF. We identified a specific DNA-binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
188
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(201 citation statements)
references
References 46 publications
10
188
2
1
Order By: Relevance
“…The third explanation is an implication of the reciprocal RARa/PLZF product, whose mRNA is found in all t(11;17) patients. This putative reciprocal fusion protein contains the ®ve C-terminal zinc ®ngers, was recently shown to be transforming and to bind DNA (Li et al, 1997;Sitterlin et al, 1997), and could thus, through competition with wild type PLZF, alter normal PLZF function. Indeed, normal PLZF could be delocalized by either PLZF/RARa or PML/RARa; in the t(11;17) cases, the few normal PLZF polypeptides which are not trapped by PLZF/ RARa could be chased from their recognition sites by RARa/PLZF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third explanation is an implication of the reciprocal RARa/PLZF product, whose mRNA is found in all t(11;17) patients. This putative reciprocal fusion protein contains the ®ve C-terminal zinc ®ngers, was recently shown to be transforming and to bind DNA (Li et al, 1997;Sitterlin et al, 1997), and could thus, through competition with wild type PLZF, alter normal PLZF function. Indeed, normal PLZF could be delocalized by either PLZF/RARa or PML/RARa; in the t(11;17) cases, the few normal PLZF polypeptides which are not trapped by PLZF/ RARa could be chased from their recognition sites by RARa/PLZF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far this di erence was attributed to the divergent N-terminal fusion partners. Through its POZ domain, PLZF is a transcriptional repressor (Li et al, 1997), and was recently shown to bind the SMRT co-repressor (Dhordain et al, 1997;Hong et al, 1997). PLZF, like PML, displays growth suppressive properties and has a nuclear speckled localization, which upon fusion to RARa becomes microspeckled .…”
mentioning
confidence: 99%
“…It is of interest that RARa-PLZF appears to be expressed in all t(11;17)(q23;q21) patients, and that it also contains the N-terminal RARa transactivating domain juxtaposed to a DNA binding domain. Since RARa-PLZF seems to play a role in APL pathogenesis by acting as a trans dominant activator of PLZF responsive genes (Li et al, 1997); Sitterlin et al, 1997), it is possible that RARa-NPM might also act as a second, dominant interfering gene in t(5;17)-associated APL. In this study, as well as in the previous t(5;17) APL report, the N-terminal portion of NPM is joined to the essential functional domains of RARa.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 100% of APL cases are associated with a t(15;17)(q22;q21) translocation that fuses RARa to the promyelocytic leukemia gene (PML) at chromosome 15q22 (de The et al, 1990(de The et al, , 1991Alcalay et al, 1991;Goddard et al, 1991;Kakizuka et al, 1991). The resulting PML-RARa gene is invariably expressed in t(15;17) APL (Castaigne et al, 1992;Grignani et al, 1994) in comparison to the reciprocal RARa-PML gene which is expressed in approximately 80% of cases (Alcalay et al, 1992;Borrow et al, 1992;Grimwade et al, 1996;Li et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It recognizes speci®c DNA sequences via its C-terminal zinc ®nger domain consisting of nine KruÈ ppel-like C2H2 elements (Li et al, 1997). However, PLZF does not function as a transactivator; rather, target genes are suppressed upon DNA binding by the interaction of the N-terminal POZ domain with the co-repressors N-CoR, SMRT, Sin3A and HDAC1 (histone deacetylase 1; Hong et al, 1997;He et al, 1998;Lin et al, 1998;Grignani et al, 1998;David et al, 1998).…”
Section: Introductionmentioning
confidence: 99%